The histone deacetylase inhibitors MS-275 and SAHA suppress the p38 mitogen-activated protein kinase signaling pathway and chemotaxis in rheumatoid arthritic synovial fibroblastic E11 cells - Choo, Q.-Y. (2014)
10.3390/molecules181114085